The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1590/s1415-47572008000400013
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms at the leptin receptor gene in three beef cattle breeds

Abstract: The genetic diversity of a single nucleotide polymorphism (SNP) at the exon 20 (T945M) of the leptin receptor gene (LEPR) and of three short tandem repeats (STRs BM7225, BMS694, and BMS2145) linked to LEPR was investigated in three beef cattle herds (Brangus Ibagé, Charolais, and Aberdeen Angus). A cheap and effective new method to analyze the T945M polymorphism in cattle populations was developed and the possible role of these polymorphisms in reproduction and weight gain of postpartum cows was evaluated. Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
4
1
1
Order By: Relevance
“…Few studies exist on LEPR gene in cattle. The SNP here considered was shown to be associated with leptin concentration during late pregnancy in Friesian breed (Liefers et al, 2004), while no relationships with daily gain were found in Aberdeen Angus and Charolais breeds (Almeida et al, 2008). In opposition to the findings in beef cattle, the present study revealed that the LEPR had the largest effect on daily gain.…”
Section: T-g-c Vs C-g-c C-c-t Vs C-g-ccontrasting
confidence: 99%
“…Few studies exist on LEPR gene in cattle. The SNP here considered was shown to be associated with leptin concentration during late pregnancy in Friesian breed (Liefers et al, 2004), while no relationships with daily gain were found in Aberdeen Angus and Charolais breeds (Almeida et al, 2008). In opposition to the findings in beef cattle, the present study revealed that the LEPR had the largest effect on daily gain.…”
Section: T-g-c Vs C-g-c C-c-t Vs C-g-ccontrasting
confidence: 99%
“…However, studies of LEPR gene polymorphism association with other characters are available; for example, Komisarek (21) reported that daughters of bulls with the TC genotype at T945M of the LEPR gene had a lower age of first insemination compared to daughters of CC homozygotes in Holstein-Friesian cattle. Almedia et al (22), in a study of 3 beef cattle breeds, observed that STR BM7225*98 was present only in the Charolais breed, and BMS 694*149 and BMS 694*153 were seen in the Brangus-Ibage breed. They further reported that these variations, along with variation at T945M, had no association with postpartum cow milk production.…”
Section: Discussionmentioning
confidence: 97%
“…However, in Y1138S LEPR-B mutant females in mice, this mutation induced impaired STAT3 signalling with residual STAT5 function, but it did not cause infertility [ 52 ]. In livestock species, Almeida et al [ 53 ] investigated the SNP (T945M) polymorphism in exon 20 of the LEPR gene in Angus, Brangus and Charolais cattle and found no associations with reproductive characteristics. The authors reported that blood leptin levels were influenced by this LEPR SNP in late pregnancy but not during lactation.…”
Section: Discussionmentioning
confidence: 99%